Test Fonetico per la Prima Infanzia (TFPI): A New Instrument to Assess Italian Toddlers’ Phonetic Development - Claudio Zmarich; Sabrina Bonichini; Marta Motterle; Maria Palmieri; Emanuela Sanfelici; Serena Bonifacio (Languages)
The purpose was to contribute to the validation of the TFPI, a new tool to assess the phonetic development of Italian-speaking children aged 18–47 months. Since currently norm-referenced instruments for Italian are lacking, the TFPI would fill this gap. We recruited 52 monolingual children aged 24–47 months with typical development. They were administered the complete TFPI, i.e., a naming task and repetition task; however, only their performances from the naming task were analyzed. The sessions were audio-recorded, in order to be later segmented and annotated in Praat, then manually transcribed with IPA. These data were then imported into Phon, an extremely suitable software for conducting analyses of phonological and speech data. We compiled the Phonetic Inventory (PhI) and calculated the Percentage of Consonants Correct (PCC) for each child, taking into consideration the allophones of Italian, in order to not compute them as errors. Both the PhI and the PCC improve with age, while intersubjective variability progressively decreases. Additionally, we investigated the age of the acquisition of each phone, since this domain lacks robust scientific data. Finally, our results align with previous findings, which proves the reliability and validity of the TFPI, and provides new information about the PCC, for which there are no reference values for the Italian language.